(untitled) (International Journal of Environmental Sciences, 2025)
Background: Meibomian Gland Dysfunction (MGD) is the primary cause of evaporative dry eye. Conventional treatment methods suffer from poor compliance and inconsistent outcomes. This study evaluates the efficacy of a custom-designed Meibomian Gland Massager (MGM) in improving clinical and symptomatic parameters in patients with MGD. Methods: A prospective interventional study was conducted among 106 patients with clinically diagnosed MGD. Participants underwent two weekly sessions using the MGM device, which delivers controlled heat and vibration to the eyelids. Objective parameters (Tear Break-Up Time [TBUT], Schirmer’s test) and subjective symptoms (Ocular Surface Disease Index [OSDI]) were assessed at baseline, 1 week, and 2 weeks. Results: TBUT increased significantly from a mean of 5.92s to 14.92s (p < 0.001). Schirmer’s test improved from 6.81 mm to 17.12 mm (RE) and 5.81 mm to 18.14 mm (LE). OSDI scores decreased from 21.14 to 7.53. The device was well-tolerated, with minimal adverse effects. Conclusion: The MGM is a promising, affordable, and effective intervention for MGD. It improves both objective signs and subjective symptoms, offering a standardizable and patient-compliant alternative to conventional therapies.